Colour and luminance selectivity of spatial and temporal interactions in orientation perception - Clifford, Colin W.G.; Pearson, Joel; Forte, Jason D.; Spehar, Branka (Vision research (Oxford), 2003)
Previous studies have commented upon the similar phenomenology of simultaneous and successive interactions in the perception of orientation. These similarities have been taken as evidence of common mechanisms underlying the simultaneous tilt illusion (TI) and the successive tilt aftereffect (TAE). We measured the TI and TAE for four subjects for combinations of test and inducing stimuli modulated along either the same or orthogonal axes of colour space within the L+ M+ S, L– M colour–luminance plane. The largest TI and TAE were found when test and inducer were modulated along the same axis of colour space. The TI consistently showed greater selectivity for colour/luminance than the TAE. The results are discussed in relation to the known chromatic properties of the primate visual pathways. Specifically, we suggest that both the TI and TAE involve colour- and luminance-specific neurons in primary visual cortex as well as cue-invariant mechanisms in extrastriate cortex.